2010
DOI: 10.1007/s11589-010-0723-9
|View full text |Cite
|
Sign up to set email alerts
|

Penetration characteristics of VLF wave from atmosphere into lower ionosphere

Abstract: The factors affecting the reflection and transmission coefficient of the ionosphere have been analyzed. These factors include wave frequency, incident angle, geomagnetic inclination, electron density and collision frequency in the ionosphere. The ionosphere refractive index is also analyzed. The ionosphere above 70 km is considered to be homogeneous and anisotropic, and the reflection and transmission coefficient matrix is calculated using matrix method. Simultaneously the Booker quartic equation is solved to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…How does the elec-tromagnetic wave propagate into the ionosphere? To unravel the mystery, we proposed an electromagnetic full wave propagation model to compute the capability of VLF waves into horizontal stratified ionosphere (Zhao et al, 2010).…”
Section: Propagation Model Of Electromagneticmentioning
confidence: 99%
“…How does the elec-tromagnetic wave propagate into the ionosphere? To unravel the mystery, we proposed an electromagnetic full wave propagation model to compute the capability of VLF waves into horizontal stratified ionosphere (Zhao et al, 2010).…”
Section: Propagation Model Of Electromagneticmentioning
confidence: 99%
“…When the wave penetrates the D/E region, it turns into whistler mode and propagates along the magnetic force line with small energy attenuation. Zhao SF et al (2016) found that the D/E region absorption of VLF wave increases with wave frequency, while the attenuation in the waveguide decreases with the increase of the wave frequency in the near field. Variation of the radiation power has no effect on attenuation in the waveguide, nor on D/E region absorption.…”
Section: Radio Wave Propagation In the Ionospherementioning
confidence: 99%
“…Wang et al (2009) deduced the spherical harmonic expression of electromagnetic field produced underground, aboveground and in ionosphere from underground SLF/ELF horizontal electric dipole by regarding the ground layers and ionosphere as spherical uniform sharp boundary mediums. Zhao et al (2010) developed the full-wave modeling of transionospheric propagation of very low frequency (VLF) waves which was applied to calculate the electromagnetic field in the stratified ionosphere for ground-based dipole transmitters and compared to observation. The simulation results coincide with the observations, which illustrate the reliability of the propagation model of electromagnetic waves (Shen et al 2011).…”
Section: Research On Seismo-ionosphere Coupling Mechanismmentioning
confidence: 99%